Discourse-Based Teaching in English Language Teaching at Islamic Universities in Borneo: A Critical Discourse Analysis Perspective - Fauzan, Umar; Saparuddin, Muhammad (International Journal of Membrane Science and Technology, 2023)
This critical discourse analysis aims to uncover what ideologies emerge in English language teaching at Islamic universities in Borneo, explain how discourse-based teaching is implemented, and why discourse-based teaching is necessary for English language teaching at Islamic universities in Borneo. This is qualitative phenomenological research using Fairclough’s Critical Discourse Analysis model. The primary data sources for this research are English language lecturers and college students at universities in Borneo, namely UIN Sultan Aji Muhammad Idris Samarinda, UIN Antasari Banjarmasin, IAIN Palangkaraya, and IAIN Pontianak. The researcher used several research instruments to collect the data: interviews, questionnaires, observations, and documentation. The data analysis technique used in this research is the interactive model from Miles et al. with the stages of data collection, data condensation, data display, and conclusion. This research concludes that English language education at Islamic universities in Borneo has an ideology of character development, influenced by several factors such as the shift in character values, the spirit of nationalism, and political policies of the Ministry of Religion to maintain national unity with a religious moderation agenda, and the vision to develop graduates who have solid Islamic character. In addition, English language education aims not only to master English language skills but also to compete in the era of information technology with critical thinking skills. Therefore, English language teaching at Islamic universities in Borneo is based on a discourse approach, from lesson planning and teaching implementation to teaching evaluation. This research implies that English language teaching should not only focus on English language skills or TEFL content but also on achieving learning outcomes from the goals of the study program, students’ needs, and the roles of lecturers as educators of Islamic and national character values.